PENERAPAN PENDEKATAN WHOLE LANGUAGE DALAM MENINGKATKAN KEMAMPUAN MEMBACA ANAK USIA DINI DI RA AR-RUM BATU AJI BATAM - muzaki, ahmad imam muzaki; Yuniati, Devi (Hamka Ilmu Pendidikan Islam, 2024)
Reading ability is one of the basic skills in language development. Good reading ability in early childhood improves cognitive development, creativity, insight, and trains concentration and discipline. One approach that has proven effective in improving the reading ability of early childhood is to use the Whole Language method. The purpose of this study was to examine the effectiveness of the Whole Language method in improving reading ability in early childhood. The study was conducted at RA AR-RUM Batu Aji Batam in a qualitative method approach. The subjects of the study used a sampling of 18 children in group B with an age range of 5-6 years. The results showed that the Whole Language method significantly improved reading ability. Reading activities associated with reading story books together, writing, drawing, playing with letters and words make children more active and motivated. This method is considered effective because it can present meaningful, contextual, and enjoyable reading activities.